PENGARUH PENGUNJUNG LOKASI PARIWISATA TERHADAP PENDAPATAN MASYARAKAT DI DESA TEMAJUK KECAMATAN PALOH KABUPATEN SAMBAS - Nuraini, Nuraini; Asriati, Nuraini; Khosmas, F Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This research aims to know the influence of visitors of tourism site to the public income in the village Temajuk District Paloh Sambas District. The method used in this research is a descriptive method with the form of a hyphen study research. The population in this study was 72 people and samples of 72 people. The data collection used are indirectcommunication techniques and documentary studies (visitor data). So the researcher concluded that, 1) visitors of the tourism location in the village Temajuk Paloh District Sambas District of 54.29% belong to the category enough. 2) Community income in Temajuk Village, Paloh, Sambas District, amounting to 58.79%, is categorized as sufficient. 3) Thitung of 11.751 which is greater than the value of 1994 so that Ha acceptedand Ho rejected. The coefficient of determination (R ) indicates a figure of 0.528, so that the percentage influence of visitors of tourism site to the public income in Temajuk village of Paloh district of Sambas district amounted to 52.8%. So, in conclusion, donations from visitors to the tourism site to the public income in the village Temajuk Paloh Sub Sambas District amounted to 52.8%.Keywords: Community Income, Temajuk, Visitor Tourism